International practice of rheumatoid arthritis registries. Foreign registries - Azamat Makhmudovich Satybaldyev; D E Karateev (Современная ревматология)
Review of the USA, Argentina, Australia, Japan, and European Union registries is presented. The similarities and differences between the registries in terms of populations of rheumatoid arthritis patients and the target goals are studied